NUV Star Catalog from the Lunar-based Ultraviolet Telescope Survey: First Release. (November 2016) - Meng, Xian-Min; Han, Xu-Hui; Wei, Jian-Yan; Wang, Jing; Cao, Li; Qiu, Yu-Lei; Wu, Chao; Deng, Jin-Song; Cai, Hong-Bo; Xin, Li-Ping
Abstract: We present a star catalog extracted from the Lunar-based Ultraviolet Telescope (LUT) survey program. LUT's observable sky area is a circular belt around the Moon's north pole, and the survey program covers a preferred area of about 2400 deg 2 which includes a region of the Galactic plane. The data are processed with an automatic pipeline which copes with stray light contamination, artificial sources, cosmic rays, flat field calibration, photometry and so on. In the first release version, the catalog provides high confidence sources which have been cross-identified with the Tycho-2 catalog. All the sources have signal-to-noise ratio larger than 5, and the corresponding magnitude limit is typically 14.4 mag, but can be as deep as ∼16 mag if stray light contamination is at the lowest level. A total of 86 467 stars are recorded in the catalog. The full catalog in electronic form is available online.